2021
DOI: 10.1155/2021/3941978
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Implementation of Machine Learning Models for the Prevention of Kidney Diseases (CKD) or Their Derivatives

Abstract: Chronic kidney disease (CKD) is a global health issue with a high rate of morbidity and mortality and a high rate of disease progression. Because there are no visible symptoms in the early stages of CKD, patients frequently go unnoticed. The early detection of CKD allows patients to receive timely treatment, slowing the disease’s progression. Due to its rapid recognition performance and accuracy, machine learning models can effectively assist physicians in achieving this goal. We propose a machine learning met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…[20,[25][26][27][28][29] However, these studies mostly focused on CKD prevention or identification. [21,[30][31][32][33] For mortality prediction in ESRD patients, most studies have focused on populations with only kidney transplant therapy or hemodialysis. [34][35][36] Therefore, this study intends to construct a mortality prediction model with AI for pre-ESRD and ESRD patients.…”
Section: Introductionmentioning
confidence: 99%
“…[20,[25][26][27][28][29] However, these studies mostly focused on CKD prevention or identification. [21,[30][31][32][33] For mortality prediction in ESRD patients, most studies have focused on populations with only kidney transplant therapy or hemodialysis. [34][35][36] Therefore, this study intends to construct a mortality prediction model with AI for pre-ESRD and ESRD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The National Renal Association categorizes CKD into stages depending on the occurrence of renal disorders and GFR, which is a marker of kidney function [12]. To lower the disease's high mortality rate, research should be widened and focused on the disease's early stages, diagnosing its risk group by laboratory testing, and preventing patients from progressing to the latter stages, such as dialysis, transplantation, or death [13].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%